The dynamic crosslinking between gut microbiota and inflammation during aging: reviewing the nutritional and hormetic approaches against dysbiosis and inflammaging - Chaudhary, Sakshi; Kaur, Pardeep; Singh, Thokchom Arjun; Bano, Kaniz Shahar; Vyas, Ashish; Mishra, Alok Kumar; Singh, Prabhakar; Mehdi, Mohammad Murtaza (Biogerontology (Dordrecht), 2025)
The early-life gut microbiota (GM) is increasingly recognized for its contributions to human health and disease over time. Microbiota composition, influenced by factors like race, geography, lifestyle, and individual differences, is subject to change. The GM serves dual roles, defending against pathogens and shaping the host immune system. Disruptions in microbial composition can lead to immune dysregulation, impacting defense mechanisms. Additionally, GM aids digestion, releasing nutrients and influencing physiological systems like the liver, brain, and endocrine system through microbial metabolites. Dysbiosis disrupts intestinal homeostasis, contributing to age-related diseases. Recent studies are elucidating the bacterial species that characterize a healthy microbiota, defining what constitutes a ‘healthy’ colonic microbiota. The present review article focuses on the importance of microbiome composition for the development of homeostasis and the roles of GM during aging and the age-related diseases caused by the alteration in gut microbial communities. This article might also help the readers to find treatments targeting GM for the prevention of various diseases linked to it effectively.